Provincial and Temporal Variation in Macrolide and Lincosamide Antimicrobial Use by Outpatients in Canada, 1995 to 2010 - Shiona K Glass-Kaastra; Rita Finley; Jim Hutchinson; David M Patrick; Karl Weiss; John Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Because antimicrobial use is commonly associated with the development of antimicrobial resistance, monitoring the volume and patterns of use of these agents is very important.